Bidirectional causal relationship between hypercholesterolemia and ischemic heart disease: a Mendelian randomization study - Jiang, Ying; Yu, Wenpeng; Zhou, Jianliang; Dong, Xiao (Frontiers in Cardiovascular Medicine, 2023)
Background: Ischemic Heart Disease (IHD) is a leading cause of morbidity and mortality worldwide.Hypercholesterolaemia, a metabolic syndrome distinguished by elevated cholesterol levels, is 2 positively correlated with IHD, yet the precise causal relationship between these two health conditions remains to be clearly defined.Methods: We conducted a two-sample MR analysis using genetic variants associated with hypercholesterolemia and IHD. Various statistical techniques including MR-Egger, Weighted Median, Inverse Variance Weighted (IVW), Simple Mode, and Weighted Mode were employed. We also performed sensitivity analyses to assess pleiotropy, heterogeneity, and influence of individual SNPs. Furthermore, genetic co-localization analysis was performed to identify shared genes between hypercholesterolemia and IHD.Results: Our MR study illuminated a bidirectional causal relationship between hypercholesterolaemia and ischaemic heart disease. Utilising the IVW with multiplicative random effects, upon considering IHD as the outcome, we identified an OR of 2.27 (95% CI: 1.91-2.70, p = 1.68E-20). Conversely, when hypercholesterolaemia was viewed as the outcome, the OR detected was 1.80 (95% CI: 1.58-2.05, p = 2.79E-19). These findings remained consistent across various MR methods and sensitivity analyses. Additionally, our research pinpointed four co-localised genes CELSR2, PCSK9, LPA, and APOE as integral candidates implicated in the pathogenesis of both conditions, thereby suggesting shared common genetic causal variants and offering potential targets for innovative therapeutic strategies.Conclusion: bidirectional MR studies reveal genetic evidence of a potential causal link between hypercholesterolaemia and IHD. Notably, these findings also lend credence to the less traditional hypothesis that IHD may instigate hypercholesterolaemia episodes. Moreover, co-localisation analyses intimate the presence of shared genetic causal variants, paving the way for the development of new therapeutic strategies.